Soft tissue tumors in hereditary tumor syndromes - Agaimy, Abbas (Pathologe, 2017)
Benign and malignant soft tissue tumors usually develop de novo without identifiable risk factors or predisposing conditions. However, in recent decades, soft tissue tumors have been increasingly recognized to be associated with diverse hereditary tumor syndromes as a consequence of germline mutations involving mainly tumor suppressor genes, but rarely also affecting proto-oncogenes. This is mainly the consequence of increasing application of modern genetic analysis tools, such as next-generation sequencing (NGS) and whole genome analyses. Syndrome-associated soft tissue tumors frequently show distinctive clinicopathological features and peculiarities that facilitate and potentially enhance their recognition and identification during routine surgical pathology practice. As it is not uncommon that pathologists are the first medical specialists to recognize a potential hereditary etiology of neoplastic diseases on the basis of specific pathological features, it is mandatory that pathologists be familiar with the main features that characterize those soft tissue tumors with inherited etiology, at least the most common and important of them. This review summarizes the main syndromes and their associated soft tissue tumors and discusses their characteristic pathological features that help in the recognition of hereditary syndromes.
EVALuna2:6862